Linear Growth of Rayleigh-Taylor Instability of Two Finite-Thickness Fluid Layers - 郭宏宇 王立锋 叶文华 吴俊峰 张维岩 (Chinese physics letters, 2017)
The linear growth of Ftayleigh-Taylor instability （FtTI） of two superimposed finite-thickness fluids in a gravita- tional field is investigated analytically. Coupling evolution equations for perturbation on the upper, middle and lower interfaces of the two stratified fluids are derived. The growth rate of the RTI and the evolution of the amplitudes of perturbation on the three interfaces are obtained by solving the coupling equations. It is found that the finite-thickness fluids reduce the growth rate of perturbation on the middle interface. However, the finite-thickness effect plays an important role in perturbation growth even for the thin layers which will cause more severe RTI growth. Finally, the dependence of the interface position under different initial conditions are discussed in some detail.